2018
DOI: 10.1016/j.jiph.2017.07.007
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for poor prognosis in children with refractory purulent meningitis and the discharge criteria

Abstract: This study was undertaken to investigate the relationship between cerebrospinal fluid abnormalities and prognosis in pediatric refractory purulent meningitis. Ninety cases of pediatric refractory purulent meningitis were stratified into "good" (n=33) or "poor" (n=57) prognosis groups according to the Glasgow clinical outcome scores. The symptoms, laboratory results, and prognosis were compared by using univariate and multivariate logistic regression analyses. Univariate analysis showed that poor prognosis was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
8
3
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 25 publications
2
8
3
3
Order By: Relevance
“…The development of complications was found with a higher frequency in patients with a CSF glucose levels below 45 mg/dL, as in our study, and this level was shown to be associated with hearing loss ( 8 , 10 , 19 , 20 , 25 ). Some studies reported that increased CSF protein levels were among poor prognostic factors ( 10 , 19 , 20 , 25 ), we found no significant difference.…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…The development of complications was found with a higher frequency in patients with a CSF glucose levels below 45 mg/dL, as in our study, and this level was shown to be associated with hearing loss ( 8 , 10 , 19 , 20 , 25 ). Some studies reported that increased CSF protein levels were among poor prognostic factors ( 10 , 19 , 20 , 25 ), we found no significant difference.…”
Section: Discussionsupporting
confidence: 84%
“…In some studies, leukopenia or reduced hemoglobin levels (<9 g/dL) were among poor prognostic factors. In our study, however, the presence of leukocytosis was associated with the development of complications ( 10 , 19 , 20 , 25 ). The development of complications was found with a higher frequency in patients with a CSF glucose levels below 45 mg/dL, as in our study, and this level was shown to be associated with hearing loss ( 8 , 10 , 19 , 20 , 25 ).…”
Section: Discussioncontrasting
confidence: 60%
See 2 more Smart Citations
“…Alterations in cerebrospinal fluid parameters have been identified as predictors of severe neurologic complications, including hydrocephalus. 2,14 -18 Cerebrospinal fluid glucose <2 mmol/L was identified as a risk factor for hydrocephalus in our study. However, Huo et al 2 did not reach the same conclusion in the study of children under 14 years old, which may be related to the higher cerebrospinal fluid glucose level in newborns than that in older children.…”
Section: Discussionmentioning
confidence: 46%